An Interesting Case of Post Traumatic Tibialis Anterior Muscle Herniation - Hegde, AS (Kathmandu University Medical Journal, 2015)
A muscle hernia is defined as a protrusion of the muscle belly through an acquired or congenital fascial defect. Muscle herniation through fascia is a relatively rare entity. Though predominantly asymptomatic, rarely they can be cause of vague pain in the leg, aggravated by exercises. Various conservative measures have been described for asymptomatic hernias, but treatment of symptomatic cases remains controversial. Here we present a case of symptomatic post traumatic tibialis anterior muscle herniation which was treated successfully with autologous fascia lata graft in Yenepoya Medical College, Mangalore in the month of January 2013. Muscle hernias should be kept in mind as a rare differential diagnosis whenever patients present with persisting vague leg pain with or without swelling. If conservative treatment fails, we recommend closure with autologous graft or fasciotomy to relieve the symptoms. Kathmandu Univ Med J 2013; 11(4): 332-334